2018
DOI: 10.1101/390195
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid inference of direct interactions in large-scale ecological networks from heterogeneous microbial sequencing data

Abstract: The recent explosion of metagenomic sequencing data opens the door towards the modeling of microbial ecosystems in unprecedented detail. In particular, co-occurrence based prediction of ecological interactions could strongly benefit from this development. However, current methods fall short on several fronts: univariate tools do not distinguish between direct and indirect interactions, resulting in excessive false positives, while approaches with better resolution are so far computationally highly limited. Fur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 55 publications
(80 reference statements)
2
51
0
Order By: Relevance
“…We confirmed that a different network inference tool, FlashWeave, was able to recover many of the same associations despite large differences in network size (Fig. 2) (Tackmann et al, 2019). Likely, the difference in edge number can be attributed to the tests for conditional independence used by FlashWeave to reduce the number of indirect edges.…”
Section: Resultssupporting
confidence: 71%
“…We confirmed that a different network inference tool, FlashWeave, was able to recover many of the same associations despite large differences in network size (Fig. 2) (Tackmann et al, 2019). Likely, the difference in edge number can be attributed to the tests for conditional independence used by FlashWeave to reduce the number of indirect edges.…”
Section: Resultssupporting
confidence: 71%
“…While methods and tools for the individual analysis steps, such as biological network estimation (see, e.g. [95,96] for recent contributions) and (differential)…”
Section: Discussionmentioning
confidence: 99%
“…Many inference methods have been developed to leverage compositionality with sparse solutions to mitigate the effects of this bias including REBECCA (Ban et al, 2015), SparCC (Friedman and Alm, 2012), SPIEC-EASI (Kurtz et al, 2015) and CCLasso (Fang et al, 2015), whereas others rely on probabilistic graphical models (Tackmann et al, 2019) or permutation-based methods (Faust and Raes, 2016). Variance log-ratio (VLR) is another compositionally valid association metric that does not produce spurious results.…”
Section: Association Measuresmentioning
confidence: 99%